Surface treatment in dental implants: a literature review. - Cerejo, Claudio Antônio; Lacerda, Goiava (Brazilian Journal of Implantology and Health Sciences, 2020)
Introduction: since the discovery and development of the study of osseointegration, shape, topography, texture and surface treatment of implants have emerged as a new way to improve the quality of these materials as well as osseointegration. Objective: the objective of this study was, by means of a literature review, to expose the types of surface treatment of dental implants, as well as the cellular interactions related to these materials and how it affects the speed and quality of osseointegration. Methods: the study was developed by means of a bibliographic survey in the Lilacs, Medline, SciELO and Bireme databases, using surface treatments, osseointegration, dental implants and implant surface as keywords. Literature review: the surface roughness and the high degree of hydrophilicity are capable of improving the results of osseointegration. Furthermore, surfaces subjected to acid attack and blasting, as well as chemically modified, present satisfactory clinical results in early loading, low bone quality and systemically compromised patients. Final considerations: although studies have shown that implants with a rough surface have a greater contact area between bone tissue and the external portion of implants, the literature does not have a consensus on the best type of surface treatment.